PARTISIPASI MASYARAKAT DALAM PENYUSUNAN PERATURAN DESA - Irwansyah, Novi (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
This study aims to examine community participation in the preparation of Village Regulations in Tepas Village, West Sumbawa Regency. The research method uses a case study approach with data collection techniques through interviews, observations, and documentation. The results of the study indicate that community participation in the preparation of Village Regulations is still formal and less substantive, with the dominance of the village government and local elites reducing the active role of residents, especially women, youth, and the poor. The low legal literacy of the community and the weak role of the Village Consultative Body (BPD) are the main obstacles, so that village deliberations have not been carried out openly and inclusively. Therefore, it is necessary to increase community legal literacy, strengthen the role of the BPD, and empower vulnerable groups so that they can participate more actively. The village government is also expected to create a dialogic and open deliberation atmosphere so that residents' aspirations can be accommodated properly and carry out periodic monitoring to improve the participation process so that the resulting Village Regulations are more legitimate and in accordance with community needs.